Metodologi Pendidikan Islam: Memahami Konsep Dasar Dan Perannya Dalam Meminimalisir Pengaruh Buruk Perkembangan Teknologi - Setiawan, Didy (Universitas Muhammadiyah Tangerang, 2023)
The rapid of technological developments has brought about many influences, both positive and negative. Also in education, technology has provided many benefits to the course of the learning process, such as bringing up innovative ways of learning and varied learning media that support the effectiveness and efficiency of achieving learning goals. However, tecnological developments surely have a negative effect on education such as the excessive use of gadgets for playing games which affect the decreased student’s focus learning. Education has an important role in providing students with understanding of how to use technology properly. In the course of education regarding the use of technology, it is necessary to have an appropriate teaching method. Therefore this artcle aims to reveal the basic concept of Islamic education methodology and its role in reducing negatif influence of technological developments. As for the research’s type used in this article is library research. The result of this research is a description of the basic concept methodology education, either general education or Islamic education. This research revealed how the important role of Islamic education methodology in reducing the negative influence of technological developments as one of the important components in achieving Islamic educational goals. On the some educational methods, either general education or Islamic eduation is obtained the the appropriate method to be used for reducing the negative influence of technological development, among other: methods of lectures, demonstration method, insert method, method of matching, and method of advice.